FORMATION OF DIAMOND POLYCRYSTALS IN PYRRHOTITE-CARBONIC MELT: EXPERIMENTS AT 6.7 GPA - Shushkanova A.V.; Litvin Yu.A. (My University, 2006)
The first syntheses of diamond polycrystals in pyrrhotite–carbonic melts are reported in this communication. The results obtained are directly related to the issue of diamond origin in the Earth’s mantle, because pores in some natural polycrystalline varieties of diamond contain not only silicate, oxide, metallic, and other phases but also sulfide minerals. However, the experimental data showed that natural sulfide melts may serve (although, to a limited extent) as a medium for the growth of diamonds, but the main role belongs to carbonate–silicate (carbonatite) melts.